Collector's guide to art deco - Miller, Judith (London : Dolrling Kindersley book, 2005)
Barware, clocks, dresser accessories, lamps, smoking items, statues, tableware and vases are among the Art Deco items covered in this comprehensive guide. In this revised second edition, the author has updated all of the values from the first edition and doubled the number of examples. 600 color photos.